Regionalism in the Mekong - Chheang, Vannarith (H. : ĐHQGHN, 2019)
The paper discusses the evolution of regionalism in the Mekong region through the lens of liberal institutionalism. It argues regional institutions and mechanisms play a critical role in promoting regional cooperation, especially in socio-economic development andpoverty reduction,infrastructure development and connectivity, and environmental cooperation. Regional institutions have contributed significantly to promoting a culture of cooperation, trust building, common interests, and the socialization of norms-based regional cooperation. However, enhancing, synergizing, and harnessing regional institutions are required to better deliver the results of regional institutions.